2019
DOI: 10.3389/fcell.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibition Activates Autophagy-Lysosome Pathway Associated With TFEB Dephosphorylation and Nuclear Translocation

Abstract: Ubiquitin-proteasome pathway (UPS) and autophagy-lysosome pathway (ALP) are the two major protein degradation pathways, which are critical for proteostasis. Growing evidence indicates that proteasome inhibition-induced ALP activation is an adaptive response. Transcription Factor EB (TFEB) is a master regulator of ALP. However, the characteristics of TFEB and its role in proteasome inhibition-induced ALP activation are not fully investigated. Here we reported that the half-life of TFEB is around 13.5 h in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 45 publications
(54 reference statements)
5
42
0
Order By: Relevance
“…This is in line with studies indicating a reciprocal regulation between the two cell-clearing systems, with UPS behaving as a sentinel in sensing and regulating autophagy, and vice versa [68,[108][109][110][111][112][113]. In detail, UPS regulates the duration and amplitude of the autophagy response by controlling the stability of Unc-51 like autophagy activating kinase (ULK1)/Atg1 complex as well as mTOR and transcription factor EB (TFEB) kinases [108][109][110]. ULK1 acts at multiple steps of autophagy initiation and response, in part by phosphorylating autophagy proteins such as Atg13, Beclin 1, and Atg9 [114].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with studies indicating a reciprocal regulation between the two cell-clearing systems, with UPS behaving as a sentinel in sensing and regulating autophagy, and vice versa [68,[108][109][110][111][112][113]. In detail, UPS regulates the duration and amplitude of the autophagy response by controlling the stability of Unc-51 like autophagy activating kinase (ULK1)/Atg1 complex as well as mTOR and transcription factor EB (TFEB) kinases [108][109][110]. ULK1 acts at multiple steps of autophagy initiation and response, in part by phosphorylating autophagy proteins such as Atg13, Beclin 1, and Atg9 [114].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 90%
“…On the one hand, UPS inhibition promotes TFEB accumulation, de-phosphorylation and nuclear translocation, leading to an increased expression of downstream autophagy-related genes including LC3-II, cathepsin D, and LAMP1. Remarkably, despite increasing autophagosome biogenesis, UPS inhibition does not affect autophagy flux [110]. This fits with recent evidence showing that UPS activity, rather than inhibition, promotes autophagy both by fostering the nuclear translocation of TFEB, and remarkably, by degrading mTOR itself, leading to its downregulation and detachment from the lysosomes [111].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 89%
See 1 more Smart Citation
“…After treatment, the cells were harvested at 0, 2, 4, 8, and 12 h time points, respectively. The lysosomal inhibitor NH 4 Cl was applied to determine the involvement of the lysosome pathway in BACE2 degradation, while the proteasomal inhibitor N-carbobenzoxy-L-leucinyl-L-leucinyl-L-leucinal (MG-132) was applied to determine the involvement of proteasome pathway in BACE2 degradation, respectively [16,23,[28][29][30]. MG-132 and NH 4 Cl were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…The UPS and ALP were previously believed to have exceedingly distinct substrates, and they were regarded as independent proteolytic systems, but accumulating evidence has established extensive crosstalk between the two, reviewed in [ 17 ]. Several studies using human cell lines and mice have reported that pharmacological and genetic inhibition of the UPS leads to the activation of autophagy [ 18 , 19 , 20 , 21 ]. However, the blocking of autophagy has reportedly more complex and contrasting results, both inhibiting and activating UPS [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%